Faktor-Faktor Yang Mempengaruhi Financial Distress - Endriana Winda Wulandari; Jaeni Jaeni (Universitas Batanghari Jambi, 2021)
This study aims to analyze the influence of operating cash flow, leverage, liquidity, operating capacity, profitability and sales growth on the financial distress of Property and Real Estate companies on the Indonesia Stock Exchange (IDX) 2015-2019. This research is a type of quantitative research using secondary data. The sample in this study obtained as many as 26 companies, in the case of the method used is purposive sampling which is a sampling method by determining the criteria that have been determined. The data analysis method used multiple linear regression. The results of the F test show that operating cash flow, leverage, liquidity, operating capacity, profitability, and sales growth variables simultaneously affect financial distress. However, in testing the hypothesis (t-test) the operating cash flow, operating capacity, profitability and sales growth variables have no effect on financial distress, while the leverage and liquidity variables have a significant and negative effect on financial distress